Metaleptic Confessions: The Problematization of Fictional Truth in Paul Auster’s Invisible - Csató, Péter (Hungarian Journal of English and American Studies, 2022)
This essay focuses on Paul Auster’s novel, Invisible (2009), aiming to explore the text’s intricate metafictional dimensions, especially the deployment of metalepsis as the main organizing principle of its narrative structure. The author argues that the novel employs a subtle metaleptic narrative structure, which moves beyond the classical postmodernist phase of textual experimentation, and serves as a means of raising questions of ethical and existential relevance. Metalepsis is construed in the paper as a trope of transgression, whereby its epistemological and ontological functions are regarded as a means to an end, which is the problematization of the interrelation between narrative structure and ethical agency. The main contention of the article is that the novel’s surreptitiously deployed metaleptic structure results in the ontological destabilization of the narrative, which in turn undermines the epistemic function (truth-telling) of the act of confession, so its ethical purpose (atonement, absolution) remains unfulfilled. (PCS) This article is a revised version of a previously published one which originally appeared in Hungarian. See the following link: http://www.epa.hu/00000/00002/00253/pdf/EPA00002_alfold_2019_09_080-096.pdf